Oral mucosal lesions associated with betel quid, areca nut and tobacco chewing habits: consensus from a workshop held in Kuala Lumpur, Malaysia, November 25-27, 1996. - Zain, R.B.; Ikeda, N.; Gupta, P.C.; Warnakulasuriya, S.; van Wyk, C.W.; Shrestha, P.; Axéll, T. (Wiley, 1999)
A variety of betel/areca nut/tobacco habits have been reviewed and categorized because of their possible causal association with oral cancer and various oral precancerous lesions and conditions, and on account of their widespread occurrence in different parts of the world. At a recent workshop in Kuala Lumpur it was recommended that "quid" be defined as "a substance, or mixture of substances, placed in the mouth or chewed and remaining in contact with the mucosa, usually containing one or both of the two basic ingredients, tobacco and/or areca nut, in raw or any manufactured or processed form." Clear delineations on contents of the quid (areca nut quid, tobacco quid, and tobacco and areca nut quid) are recommended as absolute criteria with finer subdivisions to be added if necessary. The betel quid refers to any quid wrapped in betel leaf and is therefore a specific variety of quid. The workshop proposed that quid-related lesions should be categorized conceptually into two categories: first, those that are diffusely outlined and second, those localized at the site where a quid is regularly placed. Additional or expanded criteria and guidelines were proposed to define, describe or identify lesions such as chewer's mucosa, areca nut chewer's lesion, oral submucous fibrosis and other quid-related lesions. A new clinical entity, betel-quid lichenoid lesion, was also proposed to describe an oral lichen planus-like lesion associated with the betel quid habit.